Alterations in cardiovascular function in an experimental model of lung fibrosis and pulmonary hypertension. Issue 4 (10th February 2019) - Darwiche, Tamara; Collum, Scott D.; Bi, Weizhen; Reynolds, Julia O.; Wilson, Cory; Wareing, Nancy; Hernandez, Adriana M.; Mertens, Tinne C. J.; Zhou, Zhen; Pandit, Lavannya M.; Karmouty‐Quintana, Harry
Abstract : New Findings: What is the central question of this study? We have evaluated changes in cardiovascular physiology using echocardiography in an experimental model of lung fibrosis. What is the main finding and its importance? Remarkably, we report changes in cardiovascular function as early as day 7, concomitant with evidence of vascular remodelling. We also report that isolated pulmonary arteries were hypercontractile in response to a thromboxane A2 agonist. These findings are significant because the development of pulmonary hypertension is one of the most significant predictors of mortality in patients with lung fibrosis, where there are no available therapies and a lack of animal models. Abstract: Group III pulmonary hypertension is observed in patients with chronic lung diseases such as chronic obstructive pulmonary disease or idiopathic pulmonary fibrosis. Pulmonary hypertension (PH) develops as a result of extensive pulmonary vascular remodelling and resultant changes in vascular tone that can lead to right ventricle hypertrophy. This eventually leads to right heart failure, which is the leading indicator of mortality in patients with idiopathic pulmonary fibrosis. Treatments for group III PH are not available, in part owing to a lack of viable animal models. Here, we have evaluated the cardiovascular changes in a model of lung fibrosis and PH. Data obtained from this study indicated that structural alterations in the right heart, such as right ventricular wall hypertrophy, occurred as early as day 14, and similar increases in right ventricle chamber size were seen between days 21 and 28. These structural changes were correlated with decreases in the systolic function of the right ventricle and right ventricular cardiac output, which also occurred between the same time points. Characterization of pulmonary artery dynamics also highlighted that PH might be occurring as early as day 21, indicated by reductions in the velocity–time integral; however, evidence for PH is apparent as early as day 7, indicated by the significant reduction in pulmonary acceleration time values. These changes are consistent with evidence of vascular remodelling observed histologically starting on day 7. In addition, we report hyperactivity of bleomycin‐exposed pulmonary arteries to a thromboxane A2 receptor (Tbxa2r) agonist. Abstract :